The Effects of Mindfulness-Based Cognitive Therapy on Depression and Anxiety in Women with Premenstrual Syndrome - Panahi, Faeze (Depress Res Treat, 2016)
Objective. Little research has been done regarding the role of psychotherapy in the treatment of Premenstrual Syndrome (PMS). The aim of this study was to examine the effect of mindfulness-based cognitive therapy (MBCT) on the PMS symptoms and depression and anxiety symptoms in women with PMS. Design. In a randomized controlled trial, a total of 60 students at Mazandaran University with mild to moderate PMS who had depressive symptoms (Beck depression scores 16–47) were randomly allocated to either an experimental (n = 30) or a control (n = 30) group. The experimental group received MBCT in eight group sessions (120 min each) over 8 weeks. The control group received no intervention. All participants completed the Premenstrual Assessment Scale (PAS), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) at the beginning and the end of the study. Repeated-measure ANOVA was used to analyze the data. Results. At the end of study, the experimental and control groups showed the following scores, respectively (mean ± SD): depression, 15.73 ± 6.99 and 25.36 ± 7.14; anxiety, 16.96 ± 7.78 and 26.60 ± 9.38; and total PAS, 42.86 ± 8.02 and 58.93 ± 8.47. MBCT improved depression and anxiety symptoms and total PAS score. Conclusion. MBCT intervention is acceptable and potentially beneficial in women with PMS symptoms. Psychotherapy should be considered as a treatment option for mild to moderate PMS in women with depressive symptoms.